Pasting and Dough Rheological Properties of Ackee (Blighia sapida) Aril Flour: A Contribution to the Search for Wheat Flour Substitutes (2021)
Wheat is one of the most widely used cereals in the world. However, studies consider wheat flour doughs to be of low nutritional quality, as there is now greater public awareness of celiac disease and gluten intolerance. Therefore, consumers are demanding healthier and more varied food products. Consequently, wheat flour is being replaced fully or partially by flours from other sources with higher quality. Hence, the main objective of this work was to report the effect of blending wheat flour with ackee aril flour, until the total replacement of wheat flour, on pasting and dough rheological properties. Five different levels of blending were analyzed: wheat to ackee aril flour mass ratios of 100 : 0, 75 : 25, 50 : 50, 25 : 75, and 0 : 100. Pasting properties (pasting temperature, peak viscosity, ease of cooking, swelling power, final viscosity at 50 ° C, and thixotropy) were analyzed; and steady-state shear measurements were used to obtain consistency coefficients (K) and flow behavior indexes (n) after data was fitted to the Power Law and Herschel-Bulkley models. The gradual addition of the ackee aril flour fraction produced an increase in ash, fat, protein, and fiber content; while water and carbohydrate content showed the opposite behavior in the obtained composite flour. Consequently, the partial or full replacement of wheat flour changed the rheological properties of the produced doughs, as well as the quality of the final product. These changes were mostly related to the protein and carbohydrate content of the ackee aril flour fraction. In general, doughs showed a pseudoplastic behavior with thixotropy whose viscosity decreased as the addition of ackee aril flour was increased. Pasting properties of blends involving 25 %-75 % ackee aril flour demonstrate the feasibility of including these flours in products subjected to high processing temperatures such as canned products or even to produce chips and pasta.